Inventory Control Method of Reverse Logistics for Shipping Electronic Commerce Based on Improved Multi-objective Particle Swarm Optimization Algorithm - Yang, Wei; Xie, Qianglai; Li, Ming (Journal of coastal research, 2019)
Yang, W.; Xie, Q.L., and Li, M., 2018. Inventory control method of reverse logistics for shipping electronic commerce based on improved multi-objective particle swarm optimization algorithm. In: Liu, Z.L. and Mi, C. (eds.), Advances in Sustainable Port and Ocean Engineering. Journal of Coastal Research, Special Issue No. 83, pp. 786–790. Coconut Creek (Florida), ISSN 0749-0208. Based on the improved multi-objective particle swarm algorithm, a method of inventory control of reverse logistics for shipping electronic commerce was proposed. Through the multi-objective particle swarm optimization algorithm, the inventory of electronic commerce was distributed well, heuristic algorithm was used to get the optimal solution set conforming to the preference of decision maker. According to the target weights given by decision-maker, the utility evaluation of the optimal solution set was carried out. The maximum solution of utility evaluation value was selected as the optimal scheme to complete the inventory control of reverse logistics for shipping electronic commerce. Experimental results show that the proposed method can effectively complete the inventory control of reverse logistics for shipping electronic commerce.